Conformational, Chemical Reactivity, Thermodynamic Properties, and the SEM Study of Yohimbine Hydrochloride - Joshi, Bhawani Datt; Tandon, Poonam; Jain, Sudha (Kathmandu University Journal of Science, Engineering and Technology, 2013)
We have presented a study on structural conformation of yohimbine hydrochloride using density functional theory (DFT) method. A short description about the surface morphology with scanning electron microscopy imaging has been included. Correlation between different thermodynamic properties with variation in the temperature has been given. The global and local chemical reactivity descriptors have been calculated, from which nucleophilicity and electrophilicity of the given atomic sites in the molecule can be known.